BrahMos sebagai Instrumen Pencegahan Konvensional: Evaluasi Strategi Deterrence India terhadap Pakistan - Nia Norlyanti (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The strategic rivalry between India and Pakistan has long been shaped by the threat of nuclear escalation. However, in the post-nuclear era, India increasingly relies on strengthening its conventional deterrence capabilities through the development of advanced missile systems, including the next-generation hypersonic BrahMos II. This study examines how BrahMos II influences India’s deterrence strategy toward Pakistan, particularly in restoring the effectiveness of conventional deterrence in border conflict areas. Using a descriptive-analytical qualitative method, this research analyzes defense documents, military technology reports, and media coverage related to the development and testing of BrahMos II. The findings indicate that the decline in India’s conventional deterrence effectiveness following the May 2025 border clashes accelerated the development of BrahMos II. The analysis shows that the hypersonic system enhances three core components of deterrence: first, effectiveness, through improved capability to penetrate Pakistan’s defense systems; second, response speed, enabling rapid precision strikes; and third, multi-domain launch flexibility, which strengthens operational adaptability from air, sea, and land platforms. Overall, the study concludes that BrahMos II significantly reinforces India’s conventional deterrence posture while reshaping Pakistan’s strategic calculations in future conflict dynamics in South Asia.